TREATMENT PROTOCOLS FOR CONGENITAL SYPHILIS AND ITS EVOLUTION IN NEWBORNS IN THE MUNICIPALITY OF ANÁPOLIS FROM 2013 TO 2022 (CIPEEX, 2025)
Introduction: Due to the prevalence of Congenital Syphilis (CS) in Brazil and its impact on the survival and evolution of newborns, treatment protocols have been adapted. Therefore, the objectives of this study are to describe the protocols published by the Ministry of Health and to analyze the evolution of infected newborns. Methodology: This is an observational and analytical cross-sectional study, in which a literature review and analysis of epidemiological data from the Notification Form of the Notifiable Diseases Information System (SINAN) were performed. Results: The first CS protocol was established in 2015, with modifications over the years to optimize treatment. During the penicillin shortage, alternatives such as ceftriaxone were adopted. The data show a variation in diagnosed cases, with a significant increase in 2018 and 2022. The survival of newborns improved despite the lack of penicillin, highlighting the effectiveness of the protocols implemented. Conclusion: It is clear that maintaining continuous surveillance and adequate treatment of newborns affected by CS has an impact on the incidence and prevalence of cases.
Keywords: Congenital Syphilis; Newborn; Brazil; Protocols